2011
DOI: 10.1039/c1ee01029h
|View full text |Cite|
|
Sign up to set email alerts
|

The global technical and economic potential of bioenergy from salt-affected soils

Abstract: An analysis of bioenergy production on salt-affected land indicates that this type of degraded land has a considerable technical and economic potential for sustainably producing bioenergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
198
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(202 citation statements)
references
References 28 publications
1
198
2
1
Order By: Relevance
“…They concluded that worldwide, more than 76 3 10 6 ha of land was salt-affected. More recently, Wicke et al (2011) estimated that, globally, 1.1 3 10 9 ha of land was salt-affected and 14% (1.5 3 10 8 ha) of this area is classified as forest, wetlands, or other legally protected area. Given that wetlands cover only 5.3-12.8 3 10 8 ha globally (Zedler and Kercher 2005), these numbers suggests a substantial portion of wetlands may be salt affected.…”
Section: The Global Extent Of Salinizationmentioning
confidence: 99%
“…They concluded that worldwide, more than 76 3 10 6 ha of land was salt-affected. More recently, Wicke et al (2011) estimated that, globally, 1.1 3 10 9 ha of land was salt-affected and 14% (1.5 3 10 8 ha) of this area is classified as forest, wetlands, or other legally protected area. Given that wetlands cover only 5.3-12.8 3 10 8 ha globally (Zedler and Kercher 2005), these numbers suggests a substantial portion of wetlands may be salt affected.…”
Section: The Global Extent Of Salinizationmentioning
confidence: 99%
“…Currently, 1,030 million hectares (Mha) are affected by twin problems of salinity and sodicity, of which 412 Mha are affected by salinity and 618 Mha by sodicity (Wicke et al, 2011).These estimates do not present the area where both salinity and sodicity problems occur together. The salinity problems are the result of both natural (primary salinity) and human-induced (secondary salinity) processes.…”
Section: Introductionmentioning
confidence: 98%
“…The salinity problems are the result of both natural (primary salinity) and human-induced (secondary salinity) processes. Secondary salinity affects 76 Mha, which are distributed in different continents highest being in Asia (53 Mha) (Dregne et al,1991;Wicke et al, 2011).Out of the total 76 Mha, 43 Mha are in irrigated lands of (semi-) arid regions of the world whereas the rest 33 Mha are in non-irrigated lands. Secondary salinization has resulted due to the poor water management practices in irrigated lands and clearing of deep-rooted native vegetation in rainfed areas (Marcar et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the economic benefits from saline water recycling and reuse and reversing salt-induced land degradation, there are notable environmental benefits such as mitigating climate change impacts (Wicke et al, 2011). For example, during salt-induced degradation, salt-affected lands lose a significant fraction of their original carbon pool (Ivits et al, 2013) and biomass productivity potential (John et al, 2005).…”
Section: Potential Benefits From Saline Water and Salt-affected Landmentioning
confidence: 99%